Diversifikasi Produk Olahan Tepung Inovasi Risol Kekinian Untuk Meningkatkan Pendapatan UMKM Lokal - Sulastri; Arivetullatif; Azuxetullatif; Fathiah; Maharani Putri; Rini afrianti; Yanti Murni; Irni Yusnita (CV. ITTC INDONESIA, 2026)
This community service activity aims to improve the skills and income of MSMEs in Cubadak Air Selatan village through diversification of risol products. The methods used were training, mentoring, and hands-on practice in making risol with contemporary fillings such as smoked beef, mayo, egg, sausage, vegetables, and cheese. Results showed that 80% of participants were able to produce risol independently and will market these risol product variants both online and offline. Training on simple calculations for determining cost of goods sold and how to determine selling prices was also provided. This was done to provide participants with the understanding and skills to determine appropriate selling prices and income. This activity demonstrates that innovation in processed flour products can be an effective strategy for strengthening household economies.